Enjoyment and Affective Responses to Moderate and High-Intensity Exercise: A Randomized Controlled Trial in Individuals with Subsyndromal PTSD - Daniel R. Greene; Angelia M. Holland-Winkler; Steven J. Petruzzello (MDPI AG, 2024)
This crossover randomized controlled trial examined the acute psychological effects of a bout of moderate-intensity continuous aerobic exercise (MICE) and a bout of high-intensity functional exercise (HIFE), relative to a no-exercise sedentary control (SED), in participants (N = 21; 15 f; 24.7 ± 9.3 years) with subsyndromal post-traumatic stress disorder (PTSD). Affective state (Energy, Tiredness, Tension, Calmness) was assessed before (Pre), immediately after (Post 0), 20-min after (Post 20), and 40-min after (Post 40) each condition. Affective valence was assessed during each condition, and exercise enjoyment was assessed at Post 0. Enjoyment was significantly greater following HIFE and MICE relative to SED. Energy was significantly increased Post 0 HIFE and MICE but decreased Post 0 SED. Tension was reduced following all conditions and was significantly lower at Post 40 relative to Pre for HIFE, MICE, and SED. Tiredness was significantly reduced at Post 40 relative to Pre following MICE only, while Calmness was significantly lower at Post 40 relative to Pre following MICE and SED. Overall, both exercise conditions were enjoyed to a greater extent than the control, but MICE may provide greater psychological benefits with respect to Calmness and Tiredness. This study is among the first to assess acute changes in affective states relative to various exercise modes in individuals living with subsyndromal PTSD.